HATE SPEECH AND ETHNO-RELIGIOUS CONCLICTS IN NIGERIA: Implications for Political Stability - Nkechi G. Onah; Innocent A. Ugwu; Favour C. Uroko (Scriptura Indonesia, 2021)
While freedom of expression or free speech is a fundamental human right of all, hate speech heralds danger for a country. Using a qualitative research approach, this study examines the connection between hate speech, ethnoreligious conflicts, and political stability in Nigeria. This study argues that the threat to internal security in Nigeria is a resultant effect of social injustice in the country. In Nigeria, hate speech has been on the increase instigating ethnic and religious sentiment, mistrust, and conflicts. The study suggests that peace social justice and political inclusion should be adopted in running the affairs of the nation.